Effect of Wu Qin Xi exercises on pain and function in people with knee osteoarthritis: A systematic review and meta-analysis - Guo, Jiale; Peng, Caiju; Hu, Ziyan; Guo, Liangliang; Dai, Ru; Li, Yehai (Frontiers in Medicine, 2022)
(1) Background: As a chronic disease that affects the whole world, there is no definite treatment for knee osteoarthritis. WQX is still in preliminary exploration as a traditional Chinese exercise in the treatment of osteoarthritis of the knee. The purpose of this study was to conduct a meta-analysis of previous studies and to investigate the efficacy of WQX exercises on pain function in patients with knee osteoarthritis. (2) Methods: We searched six databases (Pubmed, Embase, Cochrane Library, Wanfang, CQVIP and CNKI) for articles on WQX for knee osteoarthritis up to May 10, 2022. Literature search, study selection, data extraction and quality evaluation by two independent authors. In terms of statistical results, we present MD, 95% CI, and I2 to show heterogeneity and, based on that, choose between a random effects model or a fixed effects model. (3) Results: Seven studies were selected for inclusion in this meta-analysis. Both for the total WOMAC score and its various bylaws, VAS scores, and the presence of general functional exercise in the control group, the WQX intervention group showed statistical differences. In addition, we demonstrated clinically meaningful efficacy of WQX treatment by calculating MCID values that met the MCID values on the WOMAC score. In this process, a sensitivity analysis was also performed by subgroup analysis for greater heterogeneity, and it was inferred that the difference in follow-up time was a likely source of heterogeneity. (4) Conclusions: Despite some shortcomings, the current study shows a definite effect of WQX in improving pain symptoms joint function in patients with knee osteoarthritis.